Intellectual Disability and Hemizygous GPD2 Mutation. Issue 5 (29th March 2013) - Barge‐Schaapveld, Daniela Q.C.M.; Ofman, Rob; Knegt, Alida C.; Alders, Mariëlle; Höhne, Wolfgang; Kemp, Stephan; Hennekam, Raoul C.M.
Abstract We report on a 25‐year‐old female with intellectual disability, mildly unusual face, and a pervasive developmental disorder, in whom routine aCGH showed a 298 kb de novo deletion at chromosome 2q24.1(156869529–157167986 × 1). The region contained two genes (NR4A2; GPD2). Molecular studies in the proposita showed an additional variant in GPD2 (c.614C > T, p.Pro205Leu), which was predicted to be pathogenic. The variant was also present in the healthy mother and sister. Functional analysis showed absent GPD2 activity in the proposita and 50% activity in mother and sister. We conclude that we have been able to find circumstantial evidence for the causative effect of the hemizygous GPD2 mutation but full proof remained lacking. Total costs for the work‐up in these patients were high (€21, 975 [27, 029]). Similar results will increasingly be found when Next Generation Techniques will be applied widely in patients with intellectual disability, and proving pathogenicity by functional studies or in animal models will be expensive. We advocate the use of freely accessible international databases combining phenotype and genotype data using standard nomenclatures to facilitate proving pathogenicity of research data and to decrease costs of health care. © 2013 Wiley Periodicals, Inc.